Systematic in vivo analysis of the intrinsic determinants of amyloid Beta pathogenicity. - Leila M Luheshi; Gian Gaetano Tartaglia; Ann-Christin Brorsson; Amol P Pawar; Ian E Watson; Fabrizio Chiti; Michele Vendruscolo; David A Lomas; Christopher M Dobson; Damian C Crowther (PLoS Biology, 2007)
Protein aggregation into amyloid fibrils and protofibrillar aggregates is associated with a number of the most common neurodegenerative diseases. We have established, using a computational approach, that knowledge of the primary sequences of proteins is sufficient to predict their in vitro aggregation propensities. Here we demonstrate, using rational mutagenesis of the Abeta42 peptide based on such computational predictions of aggregation propensity, the existence of a strong correlation between the propensity of Abeta42 to form protofibrils and its effect on neuronal dysfunction and degeneration in a Drosophila model of Alzheimer disease. Our findings provide a quantitative description of the molecular basis for the pathogenicity of Abeta and link directly and systematically the intrinsic properties of biomolecules, predicted in silico and confirmed in vitro, to pathogenic events taking place in a living organism.